Influence Celebrity Endorser Atta Halilintar on Purchasing Decisions Through Brand Image as an Intervening Variable on Byond Productsby Indonesian Islamic Bank - Muhammad Fadillaturohman; Maulina Larasati Putri; Wiratri Anindhita (Prodi Ilmu Komunikasi UTM, 2025)
The rapid development of digital technology has changed the marketing landscape and promotional strategies in Indonesia. One of the prominent phenomena is the use of celebrity endorsers as an effective marketing communication strategy to improve brand image and encourage consumer purchasing decisions. BSI utilizes a marketing strategy through celebrity endorsers as its communication media. Atta Halilintar, as one of the influencers with a large follower base on social media, is believed to be able to provide a significant influence on consumer purchasing decisions, especially among the younger generation. However, this communication strategy of using celebrity endorsers raises important questions about the extent to which Atta Halilintar is effective in influencing consumer purchasing decisions for BYOND products. The study was conducted using a quantitative method through questionnaire data collection and mediation data processing with Smart PLS.03, based on a sample size of 100 taken using a random sampling method from 1,1 million Instagram followers of the Bank Syariah Indonesia account. The results of the study show that there is a significant influence of mediation between the application of the Celebrity Endorser variable as variable X on the Purchase Decision as variable Y through Brand Image as variable Z. This is proven by the results of the hypothesis test that Ho1 is rejected and Ha1 is accepted with a T-statistic value of 2.908 T-table 1.660 or an influence through mediation of 10% and a P-Value of 0.004 0.05